Diatom growth, biogenic silica production, and grazing losses to microzooplankton during spring in the northern Bering and Chukchi Seas. (September 2021) - Krause, Jeffrey W.; Lomas, Michael W.; Danielson, Seth L.
Abstract: It is unclear how warming polar marine systems will alter the magnitude of diatom productivity and its fate within the food web. We examined diatom productivity and size-fractionated phytoplankton grazing losses to protozoan grazers in the northern Bering and Chukchi seas during June 2017. Sea ice was nearly absent and water temperatures were unseasonably warm; such conditions may be considered normal in future decades. Among 28 experiments conducted, five were in bloom conditions. Diatom biomass and production rates were similar to previous studies, suggesting the early ice retreat did not lead to appreciably reduced diatom growth. Statistical analyses showed that 77% of the variance in diatom growth rate could be explained by a combination of nutrients, light, and their interaction, but the interactive effect was most important (explaining 66% of the variance). Protozoan grazing intensity on phytoplankton was largely affected by size, specifically, grazing on larger phytoplankton (e.g. diatoms) was highly variable among stations, with many stations having unquantifiable rates. Protozoan grazers consumed an average of 23 ± 35% of growth at bloom stations and 55 ± 102% among non-bloom stations. For smaller phytoplankton, grazing was persistent and less variable spatially, consuming 64 ± 38% of growth at bloom stations and 79 ± 63% at non-bloom stations. Although previous studies (that did not size-fractionate samples) inferred that protozoan grazers control diatom biomass during blooms, our results suggest that diatom productivity largely escaped protozoan grazing losses, especially in bloom conditions, likely due to temporal lag between phytoplankton and protist biomass accumulation. Thus, during bloom conditions, it was estimated that 20–50 times more diatom organic matter was available for higher trophic levels and/or export (as opposed to water column remineralization) than under non-bloom conditions, despite only a 12-fold increase in gross diatom production in the bloom.